PENGARUH PENGALAMAN, INDEPENDENSI, SKEPTISME PROFESIONAL AAUDITOR DAN PENERAPAN ATURAN ETIKA TERHADAP PENDETEKSIAN KECURANGAN (Studi Empiris Pada KAP di Pekanbaru, Padang dan Batam) - Putri Annisa; Amries Rusli Tanjung; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the effect of experience, independence, profesional skepticism of auditors and the application of ethical rules to detection of fraud (empirical studies on public accounting firm in Pekanbaru, Padang and Batam.The methods used in this research was multiple linear regression. Testing the validity and reliability questionnaire in this study using SPSS(Statistical Product and Service Solution). The sampling methods used was purposive sampling which counted 21 in 2016. Respondents used in this study were partners, managers, supervisors and senior and junior auditors. Data collected by distributing questionnairs to 105 auditors working in 21 Public Accounting Firm, but only 80 questionnaires were returned and can be processed. The results of the hypothesis test showed that experience, independence, skepticism professional of auditors and application of ethical rules has an effect on auditors performance with 0.001, 0.017, 0,000 and 0,004 significance.Keywords : experience, independence, skepticism professional auditors, application of ethical rules, detection of fraud